Proposal for working with phonetic-phonological aspects through Problem Based Learning - Machry da Silva , Susiele (2022)
Social transformations and the velocity of information have changed the language teaching scenario, bringing new challenges and the need to rethink pedagogical practice. The need for teaching in consonance with the new reality brings changes to the pedagogical practice in the postmodern era of language teaching, in which, not necessarily, a single method or approach is followed. In this new paradigm, the teacher’s role is to create their own method, based on different teaching approach. Allied to this perspective, this article presents a proposal for teaching Spanish to Brazilians using Problem-based Learning (PBL). Our objective is, therefore, to understand the emergence of the Post-Method Era in language teaching (KUMARAVADIVELU, 1994; 2001), e Active Learning Methodologies ((BACICH; MORAN, 2018; MATTAR, 2017, among others), bringing suggestions to the use of PLB to teach /s/ and /z/, which are different phonemes in Portuguese, but not in Spanish. Based on this proposal, we argue that the use of PBL can lead to the problem-solving situations in which students and teachers are active participants in the process. Keywords: Problem-based learning; Active Learning Methodologies; Spanish to Brazilians.